Molecular dynamic investigation on the dissolution behaviour of fumaric acid crystal (Form B) in ethanol solution: article / Ahmad Iqbal Ondong - Ondong, Ahmad Iqbal (2018)
Nowadays, co-crystal had been used in pharmaceutical industry. Co-crystal is the combination of active pharmaceutical ingredient (API) and co-former. The dissolution rate of API can be improved by the co-former and it is very important to select suitable co-former for the formation of co-crystal. Fumaric acid is belong to dicarboxylic acid group can act as co-former. It is also very crucial to study the properties of the crystal before we can choose it as a co-former. So, the objectives of this study are to analyse the morphology of fumaric acid crystal (form B) and to access dissolution behaviour of fumaric acid crystal (form B) in ethanol solution. For this study, we used molecular dynamic simulation approach by using Material Studio 4.4 by ACCELERYS to achieve our objectives. The combination of dreiding forces and hirshfeld charges give the morphology of fumaric acid (form B) crystal. The shape is small needle like. There are ten important facet from the morphology which are (0 1 0), (0 1 -1), (1 -1 0), (0 0 1), (1 2 1), (1 0 0), (1 -2 0), (1 0 -1), (0 2 -1) and (1 3 1). RDF and MSD analysis show that facet (0 1 -1) is interact and dissolve first in ethanol solution.